A Phase II Trial of Capecitabine Concomitantly With Whole-Brain Radiotherapy Followed by Capecitabine and Sunitinib for Brain Metastases From Breast Cancer. (6th November 2014) - Niravath, Polly; Tham, Yee Lu; Wang, Tao; Rodriguez, Angel; Foreman, Claudette; Hilsenbeck, Susan G.; Elledge, Richard; Rimawi, Mothaffar
Abstract: Author Summary: Background: Brain metastasis from breast cancer presents a significant threat to women's health and quality of life. Capecitabine and sunitinib have shown some activity in this setting; therefore, we conducted a single-arm phase II trial with these agents. Methods: Patients with breast cancer and central nervous system (CNS) metastases received whole-brain radiotherapy concurrently with capecitabine (1, 000 mg/m 2 per day for 14 consecutive days), followed by concomitant capecitabine (2, 000 mg/m 2 per day for 2 weeks followed by a 1-week break) and sunitinib (37.5 mg daily, continuously). The primary endpoint was progression-free survival (PFS). Results: Of 25 planned patients that would be required to detect a 4-month improvement (from 5 to 9 months) in median PFS with 80% power, 12 were enrolled, and the study was then closed for slow accrual. Median PFS was 4.7 months, and median overall survival was 10 months. In the CNS, 25% had progressive disease, and 83% experienced extra-CNS progression. The most common side effects were fatigue and nausea. Conclusion: In 12 evaluable patients studied, concurrent capecitabine and whole-brain radiation followed by capecitabine and sunitinib did not extend PFS over historical rates and was associated with significant toxicity. Our study was small and closed due to slow accrual.